Restricting Justice: Political Interventions in the Home and in the Market - SCHOUTEN, GINA (Philosophy & public affairs, 2013)
Critics of the restricted conception of justice ( RCJ) argue that a theory of justice should judge individual behavior directly, even when that behavior complies with just institutions. These critics have tended to focus on two kinds of behavior that they argue should fall within the subject matter of a theory of justice: the "market-maximizing" behavior of economic agents who demand incentives to exercise marketable talents in socially beneficial ways, and the "housework-shirking" behavior of family members who distribute power and labor unequally according to gender. These critics argue that RCJ implausibly places these behaviors beyond the reach of justice. Call this the "restrictiveness objection" to RCJ. A second objection to RCJ threatens to undermine RCJ from within: this criticism alleges that RCJ is arbitrary, because the theorists who embrace it lack a principled justification for restricting the subject matter of their theories to institutions while exempting the behavior of individuals within those institutions. Call this the "arbitrariness objection" to RCJ